1988
DOI: 10.1210/jcem-67-4-817
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary Function in Growth Hormone-Deficient Patients With Pituitary Stalk Transection

Abstract: We compared 1.5 T magnetic resonance (MR) image findings with hypothalamic-pituitary function in 11 patients with idiopathic pituitary dwarfism, each of whom had a history of perinatal abnormalities, and 1 patient with posttraumatic pituitary dwarfism. MR imaging revealed transection of the pituitary stalk in all patients and the formation of an ectopic posterior lobe at the proximal stump in 9 patients, none of whom had polydipsia or polyuria. Three patients without an ectopic posterior lobe had diabetes insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
97
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 17 publications
6
97
0
1
Order By: Relevance
“…In fact, the neuroimaging findings in GHD mainly include the following: first, normal or hypoplastic pituitary gland/empty sella (ES) without anatomical abnormalities of the hypothalamus or pituitary stalk and secondly, moderate-to-severe (pituitary height %3 mm) hypoplastic pituitary gland with ectopic posterior pituitary located anywhere from the median eminence to the distal stalk (1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25). Isolated GHD is more commonly observed in the first category while multiple pituitary hormone deficiencies (MPHD) occur more frequently in the second.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the neuroimaging findings in GHD mainly include the following: first, normal or hypoplastic pituitary gland/empty sella (ES) without anatomical abnormalities of the hypothalamus or pituitary stalk and secondly, moderate-to-severe (pituitary height %3 mm) hypoplastic pituitary gland with ectopic posterior pituitary located anywhere from the median eminence to the distal stalk (1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25). Isolated GHD is more commonly observed in the first category while multiple pituitary hormone deficiencies (MPHD) occur more frequently in the second.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of these radiological findings and their endocrine spectrum is variable. In particular, MPHD is more frequently associated with ectopic posterior pituitary and anterior pituitary hypoplasia than isolated GHD (2,3,5,13,14,15,17,18,20,21,22,23,24,25). The variability between different studies can be ascribed to the degree of restriction in the studies' diagnostic criteria, to the diagnostic limits of GHD itself (transitory deficits, recovery, false positives, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of pituitary function in most patients after transesphenoidal surgery suggest that there is viable pituitary tissue preoperatively, which is transiently unable to secrete, possibly as a result of altered hypothalamic regulation'-3 . It is possible to demonstrate some preserved pituitary function with the use of synthetic hypothalamic peptides like GHRH, TRH and GnRH in patients with hypothalamic-pituitary disconnection due to pituitary stalk transection or tumors of this area 14,20 . It has been showed that the preoperative serum prolactin level is higher in patients who recovered pituitary function after adenomectomy than in those who did not 1,3 .…”
Section: Discussionmentioning
confidence: 99%
“…While patients with classical IGHD uniformly show impaired GH responses to provocative stimuli such as arginine, insulin-induced hypoglycemia, glucagonpropranolol, clonidine and L-dopy which act on pituitary gland through hypothalamus, they sometimes show adequate GH responses to Gill Schriock et al 1984 ;Takano et al 1984 ;Gelato et al 1986 ;Kikuchi et al 1988 ;Hanew et al 1991;Romer et al 1991). Therefore, hypothalamic lesions were considered to be primarily responsible for GH deficiency in some cases of IGHD.…”
Section: Discussionmentioning
confidence: 99%
“…idiopathic GH deficiency ; normal short children ; GH ; GHRH ; arginine GH are In patients with idiopathic growth hormone (GH) deficiency (IGHD), plasma responses to bolus injection of growth hormone releasing hormone ( GHRH ) variable and there are no correlations among the responses and the MRI findings of pituitary glands and pituitary stalks Rogol et al 1984;Schriock et al 1984 ;Gelato et al 1986 ;Kikuchi et al 1988;ilanew et al 1991). Therefore, the main sites of lesions in GH deficiency are not yet clear.…”
mentioning
confidence: 99%